2014
DOI: 10.2174/1874079001407010007
|View full text |Cite
|
Sign up to set email alerts
|

Acute Megakaryoblastic Leukemia in Children: Diagnosis and Management Challenges in Resource-Poor Countries

Abstract: Acute Megakaryoblastic Leukemia (AMKL) is a rare subtype of acute myeloid leukemia classified as AML M7 by the French-American-British (FAB) Leukemia Cooperative Study Group. We reviewed the records of children aged less than 18 years with AMKL during the period from January 2003 to December 2010. The diagnosis of AMKL was established on the basis of the FAB criteria and confirmed by immunophenotyping. Eight cases were assigned for this period. The incidence rate of AMKL was 5.5 % of AML. The median age at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Relapse rates varied from 10% to 83% (n=15 studies), but most relapse rates were between roughly 30% and 45% [20,21,30,[37][38][39][40]42,44,45]. The highest reported relapse rate was 83%, however the majority of patients in this study had an etoposide-omitted and cytarabine-reduced induction regimen, or received a palliative regimen [29].…”
Section: Treatment Outcomes Of Pediatric Aml In Lmicsmentioning
confidence: 98%
See 3 more Smart Citations
“…Relapse rates varied from 10% to 83% (n=15 studies), but most relapse rates were between roughly 30% and 45% [20,21,30,[37][38][39][40]42,44,45]. The highest reported relapse rate was 83%, however the majority of patients in this study had an etoposide-omitted and cytarabine-reduced induction regimen, or received a palliative regimen [29].…”
Section: Treatment Outcomes Of Pediatric Aml In Lmicsmentioning
confidence: 98%
“…The majority of the studies were retrospective cohort studies (n=26), either single center (n=23) or multicenter (n=3) [42][43][44], whereas only one study had a prospective design [45]. One study included only non-DS AMKL patients [31], and one study reported on non-DS AMKL, DS-AMKL, and non-AMKL patients [21].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulative Overall Survival of AML Patients Included in the Study leukemia is 10 times more prevalent in adults than in children, it accounts for more than 30% of all childhood cancers. Compared to other types of leukemia, AML is the most deadly (Cherkaoui et al, 2014). The NCI Cancer Registry presented the cancer incidence rates at national and regional level of Egypt in the period of time between 2008 and 2011 based upon results of National Cancer Registry Program (NCRP).…”
Section: Sall4mentioning
confidence: 99%